Critical Review of Foundational Concepts in Public Health and Medicine - Al-Anzi, Nawal Mohammed; Aldosari, Waad Saif; Alhezlool, Monirh Abdullh; Alqubayshi, Abdullah Ibrahim Mohammed; Al-Qahtani, Asma Mathkar; Alanazi, Afaf Mohammed; Al-Nefuei, Haya Saad; Alqubayshi, Fahad Ibrahim Mohammed; Alotaibi, Saad Ibrahim; Alkharshawi, Shada Abdulaziz Mohammed (Journal of Ecohumanism, 2024)
Public and Medicine are two related, specific but different areas of study that encompass the advancement of a healthier population. Public health aims to promote and prevent disease and disability in large population groups, while Medicine has mainly been disease- and illness-treatment oriented. This review aims to critically assess the history and the fundamentals behind the concepts of public health and Medicine and the challenges that confront them. Topics discussed include infectious disease spread patterns, public health, risk factors, and health organizations. The integration of public health into Medicine is mooted here as one way of dealing with modern global health problems such as epidemics, non-communicable diseases, and disparities. Recommendations are made to enhance impacts on healthcare systems, reduce health inequalities, and entwine approaches that may enhance disease prevention and treatment.